Impact of microgrooves on supersonic CO2 condensation and pressure recovery in a converging-diverging nozzle - Kapil Das Sahu; Shyam Sunder Yadav; Mani Sankar Dasgupta (Case Studies in Thermal Engineering)
As global awareness of climate change grows, innovative CO2 capture solutions are crucial for sustainability. This research explores the potential of supersonic condensation-based separation as an advanced method for CO2 capture, leveraging the principles of supersonic flow and rapid condensation. The study employs computational fluid dynamics (CFD) modeling to simulate the behavior of CO2 during the phase change process in a converging-diverging nozzle. Three nozzle wall surface conditions were examined: smooth surface, 35-μm roughness, and microgrooves (0.35 mm height, 1 mm width) on the diverging section. The CFD based results are in good agreement with experimental data from the literature. The key findings include: (1) microgrooves enhance the pressure recovery post-condensation; (2) extended nucleation regions and multiple shockwaves are observed with microgrooves; (3) The smooth wall nozzle achieves the highest liquid condensation effectiveness at 15.7 %, compared to 12.7 % for the rough wall and 12 % for the microgroove wall nozzle., indicating the highest CO2 capture efficiency with smooth walls. The microgroove geometry promoted better fluid mixing but reduced overall condensation. This research contributes to developing sustainable carbon management technologies, providing valuable insights into optimizing the nozzle design and flow dynamics for enhanced CO2 capture performance.